The Relationship Between Organizational Justice and Life Satisfaction (Field Study in a sample of teacher in primary education schools in Lattaki) - Sbera, Fouad; Kahileh, Reem; Haydar, Rasha (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed to identify the relationship between Organizational Justice and Life Satisfaction in a sample of teacher in primary education schools. The Organizational Justice content (Distributive Justice, Procedural Justice, Interactional Justice).The study was conducted on a sample of teachers in the province of Latakia numbered (304) teachers, (183) of them from the countryside and (121) from the city, these teachers were (202) females, (102) males. In order to achieve the goal of this research, the researcher used scale of the Organizational Justice and Life Satisfaction scale, The researcher reached the following conclusions: There is correlation between the Organizational Justice and Life Satisfaction among the members of the sample, but there is differences between males and females on the scale of Life Satisfaction in favor of females, the individuals, whose experiences is more than 20 years realized the distributive justice as fair more than the rest of the sample.